TUTURAN LANGSUNG DAN TIDAK LANGSUNG DALAM AL-QUR`AN - Mardjoko Idris (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
Language always has two faces. It can either have its connotative meaning or denotative one, depending on the effects that the speaker desires. This paper aims at describing the examples taken from the Koran based on the type of sentences. They are interrogative and imperative, which are used denotatively or connotatively.